2006
DOI: 10.1002/jmv.20626
|View full text |Cite
|
Sign up to set email alerts
|

HHV‐6 and HHV‐7 antigenemia related to CMV infection after liver transplantation

Abstract: HHV-6 and HHV-7 antigenemia usually occurred together with symptomatic CMV infection after liver transplantation. HHV-6 preceded CMV, but HHV-7 appeared together with CMV. Further investigation of the clinical significance of HHV-6 and HHV-7 antigenemia in organ transplant patients is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 26 publications
2
25
1
1
Order By: Relevance
“…Our symptomatic CMV incidence (34.4%) was higher (1.54-fold) than incidence reported by Humar et al (2000) that reported symptomatic CMV infection in 21.6% of the patients. Similar to this study, Härmä et al (2006) found 30% of symptomatic CMV infection during 3 first months after transplantation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our symptomatic CMV incidence (34.4%) was higher (1.54-fold) than incidence reported by Humar et al (2000) that reported symptomatic CMV infection in 21.6% of the patients. Similar to this study, Härmä et al (2006) found 30% of symptomatic CMV infection during 3 first months after transplantation.…”
Section: Discussionsupporting
confidence: 90%
“…Although we have found that symptomatic CMV infection was present in most cases of liver dysfunction and graft rejection, CMV co-infection with HHV-6 or HHV-7 and HHV-6 alone were more likely related with graft rejection than CMV alone. Härmä et al (2006) had suggested a role of HHV-6 in liver dysfunction and graft rejection (with HHV-6 antigens detected in liver biopsies in same patients). Griffiths et al (1999) found also association between liver dysfunction and graft rejection with HHV-6 and dysfunction with HHV-7.…”
Section: Discussionmentioning
confidence: 97%
“…The direct clinical manifestations due to HHV-6 include a febrile illness with or without rash, myelosuppression, hepatitis, pneumonitis and neurological diseases [33,[36][37][38] . The indirect effects attributed to HHV-6 include an exacerbation of cytomegalovirus (CMV) disease, an increased severity of hepatitis C virus (HCV) recurrence, an increased risk of other opportunistic infections, allograft dysfunction, and acute cellular rejection (Table 1) [33,36,[39][40][41][42][43][44][45] . Direct HHV-6 effects Fever and rash: The most frequently reported clinical presentation of HHV-6 infection after liver transplantation is a febrile illness that can be associated with a rash [34,36,46] .…”
Section: Clinical Syndromes Associated With Hhv-6 Infection After LIVmentioning
confidence: 99%
“…Fever and rash [36] Increased incidence and severity of cytomegalovirus disease [31,40,41] Hepatitis [33,36,49] Earlier and more severe recurrence of hepatitis C virus [42] Myelosuppression [37] Higher incidence of fungal infections [44] Pneumonitis [37] Higher incidence of opportunistic Infection [36] Neurologic illness [38,44,51] Higher incidence of allograft rejection [33,36,45,53] …”
Section: Hhv-6 Indirect Effectsmentioning
confidence: 99%
See 1 more Smart Citation